Quantum Computing Threats: Study the Potential Threats that Quantum Computing Poses to Blockchain Security - Gadge, Krutika; Borkar, Pradyna; Daduria, Shreyash; Badhiye, Sagarkumar; Sarodaya, Abhishek; Raut, Roshani (International Journal of Intelligent Systems and Applications in Engineering, 2024)
With its amazing features like entanglement and superposition, quantum computing has the potential to completely transform industries like cybersecurity. However, it also presents a serious threat to current encryption standards, which are crucial to the security of blockchain technology, raising questions about their viability. Proactive tactics are necessary to address this dual challenge. Blockchain's resilience in the quantum era depends on embracing quantum-secure consensus techniques, maintaining scalability and decentralization, and implementing transitional plans using hybrid cryptography techniques. The future of digital security is largely dependent on how the revolutionary possibilities of quantum computing are balanced with the security imperatives. This study highlights the importance of stakeholder cooperation and quantum-resistant cryptography in achieving this goal, examining the ways in which these tactics strengthen the digital environment.